2013
DOI: 10.1038/hdy.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Extensive variation at MHC DRB in the New Zealand sea lion (Phocarctos hookeri) provides evidence for balancing selection

Abstract: Marine mammals are often reported to possess reduced variation of major histocompatibility complex (MHC) genes compared with their terrestrial counterparts. We evaluated diversity at two MHC class II B genes, DQB and DRB, in the New Zealand sea lion (Phocarctos hookeri, NZSL) a species that has suffered high mortality owing to bacterial epizootics, using Sanger sequencing and haplotype reconstruction, together with next-generation sequencing. Despite this species' prolonged history of small population size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 129 publications
4
20
0
Order By: Relevance
“…We have previously shown in the NZSL that variation is limited at DQB (Osborne et al . ), in keeping with the earlier finding of Lento et al . (Lento et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have previously shown in the NZSL that variation is limited at DQB (Osborne et al . ), in keeping with the earlier finding of Lento et al . (Lento et al .…”
Section: Discussionsupporting
confidence: 93%
“…Microsatellite genotyping at 17 loci was undertaken on all the pups in this study and has been described elsewhere (Osborne ; Osborne et al . ). The R program GENHET (Coulon ) was used to calculate five different measures of microsatellite heterozygosity or homozygosity, as described in Coulon () [Mean PHt, proportion of heterozygous loci in an individual; Hs_obs, standardized heterozygosity based on the mean observed heterozygosity (Coltman et al .…”
Section: Methodsmentioning
confidence: 97%
“…The historical N e for the NZ sea lion was 9,563 or 14,694 (depending on the H e value used), which resulted in a historical census population size (N C ) in the range of 21,251-133,581 individuals (depending on the N e /N C ratio) N current is the current estimate of population size based on the IUCN redlist and N e :N current is the ratio of effective population size to the IUCN estimate, which provides information on a possible otariid-specific ratio (mean 0.14 ± 0.18 SD, all otariids, excluding the NZ sea lion) a Osborne et al (2013) b Acevedo-Whitehouse et al (2009) c See Table 1 in Robertson and Chilvers (2011) d See Table 3 in Curtis et al (2011) Polar Biol at some point in the past ( Table 1). Comparison of the historical N C values with current estimated population sizes (N current ) indicated that three species (NZ sea lion, Australian sea lion Neophoca cinerea and Galápagos sea lion Zalophus wollebaeki) have not attained the expected historical N C (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…One estimate (0.72) is based on 39 individual pups from a single breeding season at Sandy Bay breeding colony in the Auckland Islands (AcevedoWhitehouse et al 2009). The other estimate (0.66) is based on 1,351 individuals sampled over seven breeding seasons and includes live and dead pups of the year, as well as mothers and breeding male sea lions (potential fathers) from three breeding colonies on the Auckland Islands (Osborne et al 2013). When inbred individuals or close relatives are included in a sample (as is the case for the large sample size), H e has a downward bias (Weir 1989;DeGiorgio and Rosenberg 2009), which might account for the difference between the two H e values (as could sampling bias associated with a small sample size) (Fig.…”
Section: Estimation Of Historical Effective Population Sizementioning
confidence: 99%
“…In MHC class II genes, the DRB regions exhibit the most elaborate polymorphisms, and these have been extensively characterized in marine mammals, due to their importance in immunological research (Bowen et al, 2004;Osborne et al, 2013). In this study, we examined the loci within the DRB region, with emphasis on the second exon of DRB.…”
Section: Introductionmentioning
confidence: 99%